The South African building procurement strategy for public sector delivery in the Civil Engineering industry: investigating alternatives - Visser, Zwingli (Department of Construction Economics and Management, 2020)
Reports from members of the civil engineering industry in South Africa claim that the industry is struggling and that there is a drain of technical expertise from the country. Some role players blame the cost-based competitive building procurement strategy currently widely used by the public sector, while others believe the Traditional Building Procurement Strategy is to blame. This study investigates circumstances surrounding the current South African building procurement strategy to establish if there are problems with the current system, identify what those problems are and investigates what alternatives can be implemented to positively affect project delivery. A single Case study is used to interview fifteen respondents in the civil engineering industry. Interviews with municipal officials, consultants and contractors are held and the results of the interviews are analyzed. The results of the study indicate that a cost-based building procurement strategy is leading to poor project delivery and client dissatisfaction as too much focus is put on pricing and preference criteria instead of quality criteria. Contributing to the dire situation are consultants having to tender at excessive discounts to ensure the procurement of services. This also leads to a drain of technical skills in South Africa and a lack of technical capacity in Local Government to provide the necessary input during project execution. Few of the respondents have been involved in any alternative building procurement strategies. The interpretation of legislation by the municipal officials during the tender evaluation process seems to add to project delays and over-expenditure on projects and many of the respondents believe that the current strategy was developed specifically to curb corruption and therefore change is not imminent. The study concludes that the industry’s representative bodies needs play a bigger role in informing National Government of the current problems associated with public-sector delivery in order to effect policy changes. Only then it can be implemented at Local Government level to ensure an improvement in public-sector delivery.